Forests and climate change in Latin America: linking adaptation and mitigation in projects and policies - Locatelli, Bruno; Evans, V.; Wardell, A.; Andrade, A.; Vignola, Raffaele (Center for International Forestry Research, 2010)
Integrating adaptation and mitigation in forestry projects and policies would maximise local cobenefits and contribute to increased capacity to cope with the risks associated with climate change. Latin America has had some preliminary experience with the linkages between adaptation and mitigation at the level of projects. Projects should be assessed to determine their potential to include both adaptation and mitigation measures. Climate change or forest policies can facilitate the integration of adaptation and mitigation in the forest sector, but few policies in Latin America have addressed the linkages between adaptation and mitigation